The Evolution of Community-School Bully Prevention Programs: Enabling Participatory Action Research - Lorion, Raymond (Psykhe, 2004)
Community scientists must resist the temptation to solve an identified problem. Rather, they must partner with members of the community and transfer to them the knowledge and skills to understand and resolve their needs. This case-study reports a communitys efforts to reduce school-based bullying. Within a participatoryaction approach, teachers, students, administrators and parents organized to assess the ways in which members of the school-community mistreated each other. Students bullying each other was part of a larger systemic pattern in which teachers bullied each other and, with unexpectedly serious consequences, their students. Through their active participation, members of the school-community engaged together in understanding and resolving the problem.